Cd and Ni transport and accumulation in the halophyte Sesuvium portulacastrum: implication of organic acids in these processes - Mnasri, Mejda; Ghabriche, Rim; Fourati, Emna; Zaier, Hanen; Sabally, Kebba; Barrington, Suzelle; Lutts, Stanley; Abdelly, Chedly; Ghnaya, Tahar (Frontiers in Plant Science, 2015)
The implication of organic acids in Cd and Ni translocation was studied in the halophyte species Sesuvium portulacastrum. Citric, fumaric, malic and ascorbic acids were separated and quantified by HPLC technique in shoots, roots and xylem saps of plants grown on nutrient solutions added with 50 µM Cd, 100 µM Ni and the combination of 50 µM Cd + 100 µM Ni. Results showed that Cd had no significant impact on biomass production while Ni and the combination of both metals drastically affected plant development. Cadmium and Ni concentrations in tissues and xylem sap were higher in plants individually exposed to heavy metal application than in those subjected to the combined treatment Cd + Ni, suggesting a possible competition between these metals for absorption. Both metals applied separately or in combination induced an increase in citrate concentration in shoots and xylem sap but a decrease of this concentration in the roots. However a minor relationship was observed between metal application and fumaric, malic and ascorbic acids. Both observations suggest the implication of citric acid in Cd, Ni translocation and shoot accumulation in S. portulacastrum. The relatively high accumulation of citric acid in xylem sap and shoot of S. portulacastrum could be involved in metal chelation and thus contributes to heavy metal tolerance in this species.